The Roads We Take: Cellular Targets and Pathways Leading Biologics Across the Blood–Brain Barrier - Baghirov, Habib (Frontiers in Drug Delivery, 2022)
Biologics are at the frontier of CNS disease treatment. This applies both to therapeutic molecules such as peptides, antibodies, RNAi agents etc., and to delivery vehicles of biological origin such as viral vectors and extracellular vesicles. Unlike small molecules, biologics are not likely to diffuse across cell membranes. To get into and across brain capillary endothelial cells (BCEC) forming the blood-brain barrier, they normally employ active, energy-dependent processes. They can initiate these processes non-specifically or trigger them by interaction with various receptor or transporter molecules at the luminal surface of BCEC. Designing biologics to use this specific engagement is more common in smaller formats, especially peptides and antibodies, but can also apply to targeted vehicles. This targeted design has employed a number of molecules expressed on BCEC - the transferrin receptor being the most common example, although there has been progress in identifying molecules that are even more specific to BCEC. In addition, the format of biologics and a multitude of their biophysical properties affect the way they interact with BCEC, and this diversity is even more salient between different classes of biologics. It affects the entire span of interaction with BCEC, from the initial engagement at the luminal surface to intracellular sorting, and, eventually, entrapment or routing toward exocytosis into the brain parenchyma. In this paper, I review the progress in identifying novel targets that make interactions between biologics and BCEC more specific, and in our understanding of the interplay between the properties of biologics and these interactions.